Efficacy and safety of deep transcranial magnetic stimulation for major depression: a prospective multicenter randomized controlled trial. Issue 1 (February 2015) - Levkovitz, Yechiel; Isserles, Moshe; Padberg, Frank; Lisanby, Sarah H.; Bystritsky, Alexander; Xia, Guohua; Tendler, Aron; Daskalakis, Zafiris J.; Winston, Jaron L.; Dannon, Pinhas; Hafez, Hisham M.; Reti, Irving M.; et al.
<x xml:space="preserve">Abstract</x> Major depressive disorder (MDD) is a prevalent and disabling condition, and many patients do not respond to available treatments. Deep transcranial magnetic stimulation (dTMS) is a new technology allowing non‐surgical stimulation of relatively deep brain areas. This is the first double‐blind randomized controlled multicenter study evaluating the efficacy and safety of dTMS in MDD. We recruited 212 MDD outpatients, aged 22–68 years, who had either failed one to four antidepressant trials or not tolerated at least two antidepressant treatments during the current episode. They were randomly assigned to monotherapy with active or sham dTMS. Twenty sessions of dTMS (18 Hz over the prefrontal cortex) were applied during 4 weeks acutely, and then biweekly for 12 weeks. Primary and secondary efficacy endpoints were the change in the Hamilton Depression Rating Scale (HDRS‐21) score and response/remission rates at week 5, respectively. dTMS induced a 6.39 point improvement in HDRS‐21 scores, while a 3.28 point improvement was observed in the sham group (p=0.008), resulting in a 0.76 effect size. Response and remission rates were higher in the dTMS than in the sham group (response: 38.4 vs. 21.4%, p=0.013; remission: 32.6 vs. 14.6%, p=0.005). These differences between active and sham treatment were stable during the 12‐week maintenance phase. dTMS was associated with few and minor side effects apart from one seizure in a patient where a protocol violation occurred. These results suggest that dTMS constitutes a novel intervention in MDD, which is efficacious and safe in patients not responding to antidepressant medications, and whose effect remains stable over 3 months of maintenance treatment.